Islet amyloid polypeptide & amyloid beta peptide roles in Alzheimer’s disease : two triggers, one disease - Martins, Ivo C. (2021)
© Neural Regeneration Research. This is an open access journal, and articles are distributed under the terms of the Creative Commons AttributionNonCommercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.